2015
DOI: 10.1007/s10639-015-9431-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparing teachers for schooling in the digital age: A meta-perspective on existing strategies and future challenges

Abstract: Recent developments in educational innovation and new technologies have made tensions between old and new models of schooling more apparent, creating new demands upon teachers as agents of change. Looking back at the last 20 years, it is clear that important steps in development have tried to find a good balance between technology-and pedagogy-driven changes. In the first part of this article, we present some strategic models that summarize these developments. The second part of the article addresses new chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
0
12
1
4
Order By: Relevance
“…A study carried out by the Ministry of Education itself assumes that a teacher who prepares their students to cope with the challenges of the 21st century has already mastered those skills (Dayan et al, 2013). This is in contrast to studies which have found that many teachers lack this ability (Erstad et al, 2015; Wastiau et al, 2013). Nor does this approach consider the differences among teachers, stemming from personal attitudes, technological training, and their relative experience in the field.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…A study carried out by the Ministry of Education itself assumes that a teacher who prepares their students to cope with the challenges of the 21st century has already mastered those skills (Dayan et al, 2013). This is in contrast to studies which have found that many teachers lack this ability (Erstad et al, 2015; Wastiau et al, 2013). Nor does this approach consider the differences among teachers, stemming from personal attitudes, technological training, and their relative experience in the field.…”
Section: Discussioncontrasting
confidence: 97%
“…On the other hand, most of the interviewees were unable to explain the meaning of the term “information literacy” and did not sufficiently distinguish between the use of technological tools and the substantive changes required in teaching methods. They used technology mainly for screening presentations and videos, in a way that preserved traditional teaching methods (Erstad et al, 2015; Melamed, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the mechanisms of integrating media education into the professional training of teachers are being investigated (within the framework of the European project e-MEL Education Lab [12]), the analysis of models and ways of implementing promising developments in the field of IT-technologies in education [13], 5G technologies, streaming video, mixed reality, models of multilevel professional pedagogical training are being designed in the context of digitalization of education [14,15];…”
Section: Resultsmentioning
confidence: 99%
“…Con frecuencia los alumnos utilizan los medios ligados a contextos de interacción social, pero no profundizan sobre su significado, pues es algo que necesita estimulación, y aquí es donde entra el rol del profesorado ofreciendo prácticas enriquecedoras más allá de las que habitualmente desarrollan los jóvenes fuera del aula (Dussel, 2012). La actitud del docente y su grado de competencia digital es fundamental para que puedan desarrollarse estos procesos en el aula (Aguaded & Pérez-Rodríguez, 2012;Erstad, Eickelmann, & Eichhorn, 2015).…”
Section: Discusión Y Conclusionesunclassified